2003
DOI: 10.1002/app.13276
|View full text |Cite
|
Sign up to set email alerts
|

Application of chitosan‐entrapped β‐galactosidase in a packed‐bed reactor system

Abstract: ABSTRACT:The model enzyme ␤-galactosidase was entrapped in chitosan gel beads and tested for hydrolytic activity and its potential for application in a packed-bed reactor. The chitosan beads had an enzyme entrapment efficiency of 59% and retained 56% of the enzyme activity of the free enzyme. The Michaelis constant (K m ) was 0.0086 and 0.011 mol/mL for the free and immobilized enzymes, respectively. The maximum velocity of the reaction (V max ) was 285.7 and 55.25 mol mL Ϫ1 min Ϫ1 for the free and immobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…키토산은 가격이 저렴하고 독성이 없으며 화학적으로 안 정하기 때문에 크로마토그래피, 화학분석, 한외여과 그리고 여러 식품과 산업분야에서 널리 응용되고 있다. 또한 그 동안 키토산을 효소 고정화용 담체로 사용하는 시도가 있었다 [2,5,22]. 키토산 [15].…”
Section: 서 론unclassified
“…키토산은 가격이 저렴하고 독성이 없으며 화학적으로 안 정하기 때문에 크로마토그래피, 화학분석, 한외여과 그리고 여러 식품과 산업분야에서 널리 응용되고 있다. 또한 그 동안 키토산을 효소 고정화용 담체로 사용하는 시도가 있었다 [2,5,22]. 키토산 [15].…”
Section: 서 론unclassified
“…in the sample liquid [82]. It has been reported that after immobilizing an enzyme to a charged support, there can be a shift in pH optima versus that of free enzyme [83][84][85]. Zeta potential may also be useful in making conclusions about the mechanism of such shifts.…”
Section: Zeta Potentialmentioning
confidence: 99%
“…The tip moves in response to tip-surface interactions, and this movement is measured by focusing a laser beam onto the back of the cantilever and detecting the position of the reflected beam with a photodiode. Different modes of operation can be used [84].…”
Section: Zeta Potentialmentioning
confidence: 99%
“…The enzyme was reported to have stronger hydrolytic activity than transferase activity and produced a high proportion of trisaccharide in the synthetic GOS mixtures [1,2,7]. Some techniques have been developed for immobilization of ß-galactosidase including non-covalent adsorption, covalent binding, entrapment and encapsulation [1][2][3][8][9][10][11]. The newly developed synthetic micro porous membrane adsorbers as chromatographic media are an attractive alternative to traditionally used packed bed chromatography, which has several limitations [12].…”
Section: Introductionmentioning
confidence: 99%